Flame-retardant fabric and preparation method thereof
Through the blending of carrageenan fiber and viscose fiber and the addition of specific auxiliary agents, a stable residual carbon structure and a dense composite barrier are formed, which solves the problem of insufficient fire-retardant flame retardant performance of the fabric and achieves efficient flame retardant and mechanical performance improvement.
Patent Information
- Application Number
- CN202411528763.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fabrics have shortcomings in fire-retardant properties, especially in high-risk industries such as coal mines, which are difficult to meet the needs of safe production.
Using the blending and braiding technology of carrageenan fiber and viscose fiber, a stable residual carbon structure is formed by cross-linking carrageenan with barium, and a dense composite barrier is formed by dithiopyrophosphate and magnesium aluminum silicate to improve the resistance of the fabric. ignition properties, and glutamine and sodium carboxymethylcellulose are added to enhance the mechanical properties.
It significantly improves the flame retardant performance and mechanical properties of the fabric, can effectively block heat and combustible gases, delay the decomposition of the fiber matrix, and enhance the overall fire resistance of the fabric.
Smart Images

Figure BDA0005109954730000081 
Figure BDA0005109954730000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fabric preparation, and in particular to a flame retardant fabric and a preparation method thereof. Background Art
[0002] Fabrics are materials used to make clothing. Most high-quality, high-end fabrics are comfortable to wear, sweat-wicking and breathable, drape straight, look noble, and feel soft. With the continuous advancement of science and technology, people's living standards have been greatly improved, and people's requirements for the performance of clothing fabrics are getting higher and higher. In addition to paying attention to the color and style of clothing, people are paying more and more attention to the comfort, safety and other functions of clothing.
[0003] With the increasing coal production, the safety accidents in China's coal mines have attracted more and more attention from the world. In recent years, as people's awareness of environmental protection, fire protection and safety has been strengthened, fire-retardant materials (clothing) have been paid more and more attention, among which the fire-retardant of industrial textiles has become a hot topic of research. As coal mine accidents have occurred frequently in recent years, it is necessary to develop a fire-retardant fabric for use in the coal mining industry. Summary of the invention
[0004] In order to improve the flame retardant properties of fabrics, the present application provides a flame retardant fabric and a preparation method thereof.
[0005] In the first aspect, the present application provides a flame retardant fabric, which adopts the following technical solution: A flame retardant fabric, comprising a fabric body, wherein the fabric body comprises carrageenan fiber and viscose fiber; The preparation method of the carrageenan fiber comprises the following steps: The carrageenan and the sodium hydroxide aqueous solution are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution, and then the spinning solution is spun into a coagulation bath and a stretching bath, and then soaked, washed, and dried to obtain carrageenan fibers; the coagulation bath is a barium chloride aqueous solution; The method for preparing the viscose fiber comprises the following steps: The cellulose and sodium hydroxide aqueous solution are mixed, stirred evenly, vacuum degassed, and then spun to obtain viscose fiber.
[0006] By adopting the above technical solution, the fabric made of carrageenan fiber and viscose fiber has good flame retardancy for the following reasons: The sulfate groups and barium ions in the carrageenan molecule can jointly promote the cross-linking of carrageenan fibers into carbon, which is conducive to the production of a large number of stable residual carbon structures in carrageenan fibers. At the same time, the metal element barium can change the thermal decomposition process of carrageenan molecules, promote the carrageenan fibers to produce a large number of flame-retardant and non-flammable gases and residual carbon, thereby improving the flame retardancy of carrageenan fibers, and then improving the flame retardancy of fabrics.
[0007] In addition, viscose fiber has the characteristics of good air permeability and high comfort. Therefore, the fabric blended by carrageenan fiber and viscose fiber has excellent flame retardant properties and good comfort.
[0008] Preferably, the stretching bath is an epichlorohydrin solution.
[0009] By adopting the above technical scheme, the epichlorohydrin molecule contains active chlorine and epoxy groups, both of which can react with the alcohol hydroxyl groups in carrageenan to form ether bonds; epichlorohydrin can react with carrageenan to form a network cross-linked structure, thereby improving the strength of the carrageenan fiber and further improving the mechanical properties of the fabric.
[0010] Preferably, glutamine is further added during the preparation of the carrageenan fiber, and the preparation method of the carrageenan fiber comprises the following steps: The carrageenan and sodium hydroxide aqueous solution are mixed, stirred evenly, and glutamine is added, stirred evenly, and then subjected to degassing treatment to obtain a spinning solution. The spinning solution is then spun and then enters a coagulation bath and a stretching bath, and then soaked, washed, and dried to obtain carrageenan fibers. By adopting the above technical solution, glutamine is mainly accumulated in the network cross-linked structure as a filling agent, thereby reducing the holes and pore size of the network cross-linked structure, thereby further improving the strength of the carrageenan fiber.
[0011] Preferably, the mass ratio of carrageenan to glutamine is 1:(0.2-0.3).
[0012] By adopting the above technical solution, the mass ratio of carrageenan to glutamine is controlled within the above range, which can effectively improve the mechanical properties of the fabric.
[0013] Preferably, dithiodipyrophosphate and magnesium aluminum silicate are further added during the preparation of the viscose fiber, and the preparation method of the viscose fiber comprises the following steps: S1. Add dithiopyrophosphate, tallow amine polyoxyethylene ether nonionic dispersant, and castor oil polyoxyethylene ether nonionic dispersant to deionized water, and stir evenly to obtain a dithiopyrophosphate dispersion; add magnesium aluminum silicate, tallow amine polyoxyethylene ether nonionic dispersant, and castor oil polyoxyethylene ether nonionic dispersant to deionized water, and stir evenly to obtain a magnesium aluminum silicate dispersion; S2. Add cellulose to a sodium hydroxide aqueous solution, stir evenly, then add a dithiopyrophosphate dispersion and a magnesium aluminum silicate dispersion, stir evenly, vacuum degas, and then spin to obtain viscose fiber.
[0014] By adopting the above technical scheme, dithiopyrophosphate decomposes to generate phosphoric acid, which promotes the decomposition and carbonization of viscose fiber to form a carbon layer. The carbon layer and the inorganic substances (aluminum oxide and silicon dioxide) formed by magnesium aluminum silicate form a denser composite barrier, which better blocks the conduction of heat and the escape of combustible gases, delays the decomposition of the fiber matrix, and increases the amount of residual carbon. Magnesium aluminum silicate contains silicon element, which is easily migrated to the fiber surface when heated, so that the surface of the carbon layer is covered with a silicon layer, thereby improving the flame retardant properties of the viscose fiber and effectively improving the flame retardant properties of the fabric.
[0015] When magnesium aluminum silicate is mixed with viscose raw materials, due to the unique layered chain spatial structure of magnesium aluminum silicate, there are only intermolecular forces between layers, and there are a large number of gaps inside the crystal. Therefore, the cellulose macromolecular chain enters the middle of the crystal layer to form a network structure, thereby enhancing the mechanical properties of viscose fiber.
[0016] Preferably, the mass ratio of cellulose, dithiopyrophosphate and magnesium aluminum silicate is 10:(1.6-2.0):(0.4-0.6).
[0017] By adopting the above technical solution, the mass ratio of cellulose, dithiopyrophosphate and magnesium aluminum silicate is controlled within the above range, which can effectively improve the viscose fiber.
[0018] Preferably, the carrageenan fiber is prepared by modification, and the modification preparation method of the viscose fiber comprises the following steps: Sodium carboxymethyl cellulose, citric acid and sodium hypophosphite are added into deionized water, and after the reaction is completed, viscose fiber is added and dried to obtain modified viscose fiber.
[0019] By adopting the above technical solution, sodium carboxymethyl cellulose generates carboxylic acid cross-linking with viscose fiber through citric acid, so that sodium carboxymethyl cellulose is grafted onto the viscose fiber, so that the surface of the viscose fiber is negatively charged.
[0020] The surface of carrageenan fiber contains metal ions, which are positively charged. Through the principle of mutual attraction between positive and negative charges, the bonding force between carrageenan fiber and viscose fiber is effectively improved, thereby improving the mechanical properties of the fabric.
[0021] Sodium hypophosphite, as a catalyst, promotes the citric acid esterification and cross-linking. Preferably, the mass ratio of the viscose fiber to sodium carboxymethyl cellulose is 1:(0.3-0.5).
[0022] By adopting the above technical solution, the mass ratio of viscose fiber and sodium carboxymethyl cellulose is controlled within the above range, which can effectively improve the mechanical properties of the fabric.
[0023] On the other hand, the present application provides a method for preparing a flame-retardant fabric as in the first aspect, which adopts the following technical solution: A method for preparing a flame retardant fabric comprises the following steps: The flame retardant knitted fabric is produced by blending carrageenan fiber and viscose fiber.
[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. The sulfate groups and barium ions in the carrageenan molecule can jointly promote the cross-linking of carrageenan fibers into carbon, which is conducive to the production of a large number of stable residual carbon structures in carrageenan fibers. At the same time, the metal element barium can change the thermal decomposition process of carrageenan molecules, promote the carrageenan fibers to produce a large number of flame-retardant and non-flammable gases and residual carbon, thereby improving the flame retardancy of carrageenan fibers, and then improving the flame retardancy of fabrics.
[0025] 2. Dithiopyrophosphate decomposes to generate phosphoric acid, which promotes the decomposition and carbonization of viscose fiber to form a carbon layer. The carbon layer and the inorganic substances (aluminum oxide and silicon dioxide) formed by magnesium aluminum silicate form a denser composite barrier, which better blocks the conduction of heat and the escape of combustible gases, delays the decomposition of the fiber matrix, and increases the amount of residual carbon. Magnesium aluminum silicate contains silicon, which is easily migrated to the fiber surface when heated, so that the surface of the carbon layer is covered with a silicon layer, thereby improving the flame retardant properties of the viscose fiber and effectively improving the flame retardant properties of the fabric. DETAILED DESCRIPTION
[0026] The embodiment of the present application discloses a flame retardant knitted fabric, including a fabric body, wherein the fabric body includes carrageenan fiber and viscose fiber. The present application is described in detail below in combination with the embodiment and comparative example. The raw materials involved in the present application can be obtained commercially.
[0027] Example 1 The preparation method of carrageenan fiber comprises the following steps: 90 g of carrageenan and 1000 g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) are mixed, mechanically stirred in a 50° C. water bath for 2 h, poured into a raw material tank, and vacuum degassed for 0.5 h to obtain a spinning solution. The spinning solution is then passed through a metering pump under nitrogen pressure, sprayed from a spinneret, and then enters a coagulation bath and a stretching bath (stretching ratio is 1:2), and then soaked in an alcohol solution (the mass concentration of the alcohol solution is 50%), washed, and dried to obtain carrageenan fibers.
[0028] The coagulation bath includes a barium chloride aqueous solution; the preparation method of the barium chloride aqueous solution includes the following steps: adding 50g of barium chloride to 1000g of deionized water, stirring evenly, and heating to 15°C to obtain the barium chloride aqueous solution.
[0029] The stretching bath includes an epichlorohydrin solution, wherein the preparation method of the stretching bath includes the following steps: adding 100g of epichlorohydrin to 2000g of ethanol aqueous solution (the mass concentration of the ethanol aqueous solution is 95%), stirring evenly, and obtaining the epichlorohydrin solution.
[0030] The preparation method of viscose fiber comprises the following steps: 100 g of cellulose was added to 1000 g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution was 5%), stirred evenly, vacuum degassed for 1 hour, and then spun through a wet spinning machine to obtain viscose fiber.
[0031] The method for preparing a flame retardant knitted fabric comprises the following steps: The flame retardant knitted fabric is produced by blending carrageenan fiber and viscose fiber.
[0032] The mass ratio of carrageenan fiber to viscose fiber is 1:1.5.
[0033] Example 2 The difference between Example 2 and Example 1 is that glutamine is further added during the preparation of carrageenan fiber. The preparation method of carrageenan fiber comprises the following steps: The preparation method of carrageenan fiber comprises the following steps: 90g of carrageenan and 1000g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) are mixed, mechanically stirred in a 50°C water bath for 2h, 18g of glutamine is added, stirred evenly, poured into a raw material tank, and vacuum degassed for 0.5h to obtain a spinning solution, and then the spinning solution is passed through a metering pump under nitrogen pressure, sprayed from a spinneret into a coagulation bath and a stretching bath (stretching ratio is 1:2), and then soaked in an alcohol solution (the mass concentration of the alcohol solution is 50%), washed, and dried to obtain carrageenan fibers.
[0034] Example 3 The difference between Example 3 and Example 1 is that glutamine is further added during the preparation of carrageenan fiber. The preparation method of carrageenan fiber comprises the following steps: The preparation method of carrageenan fiber comprises the following steps: 90g of carrageenan and 1000g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 4%) are mixed, mechanically stirred in a 50°C water bath for 2h, and then 27g of glutamine is added and stirred evenly, and then poured into a raw material tank, vacuum degassed for 0.5h to obtain a spinning solution, and then the spinning solution is passed through a metering pump under nitrogen pressure, and then sprayed from a spinneret into a coagulation bath and a stretching bath (stretching ratio is 1:2), and then soaked in an alcohol solution (the mass concentration of the alcohol solution is 50%), washed, and dried to obtain carrageenan fibers.
[0035] Example 4 The difference between Example 4 and Example 1 is that glutamine is further added during the preparation of carrageenan fiber. The preparation method of carrageenan fiber comprises the following steps: The preparation method of carrageenan fiber comprises the following steps: 90g of carrageenan and 1000g of sodium hydroxide aqueous solution (the mass concentration of the sodium hydroxide aqueous solution is 2mol / L) are mixed, mechanically stirred in a 50°C water bath for 2h, and then 22.5g of glutamine is added and stirred evenly, and then poured into a raw material tank, vacuum degassed for 0.5h to obtain a spinning solution, and then the spinning solution is passed through a metering pump under nitrogen pressure, and then ejected from a spinneret into a coagulation bath and a stretching bath (stretching ratio is 1:2), and then soaked in an alcohol solution (the mass concentration of the alcohol solution is 50%), washed, and dried to obtain carrageenan fibers.
[0036] Example 5 The difference between Example 5 and Example 4 is that the mass ratio of carrageenan to glutamine is 1:0.1.
[0037] Example 6 The difference between Example 6 and Example 4 is that the mass ratio of carrageenan to glutamine is 1:0.4.
[0038] Example 7 The difference between Example 7 and Example 4 is that thiopyrophosphate and magnesium aluminum silicate are further added during the preparation of viscose fiber. The preparation method of viscose fiber comprises the following steps: The preparation method of viscose fiber comprises the following steps: S1, adding 16g of dithiopyrophosphate, 1.6g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.8g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a dithiopyrophosphate dispersion: adding 6g of magnesium aluminum silicate, 0.4g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.2g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a magnesium aluminum silicate dispersion; S2. Add 100 g of cellulose to 1000 g of sodium hydroxide aqueous solution (the mass concentration of sodium hydroxide aqueous solution is 5%), stir evenly, then add dithiopyrophosphate dispersion and magnesium aluminum silicate dispersion, stir evenly, vacuum degassing for 1 hour, and then spin through a wet spinning machine to obtain viscose fiber.
[0039] Example 8 The difference between Example 8 and Example 4 is that thiopyrophosphate and magnesium aluminum silicate are further added during the preparation of viscose fiber. The preparation method of viscose fiber comprises the following steps: The preparation method of viscose fiber comprises the following steps: S1, adding 20g of dithiodipyrophosphate, 1.6g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.8g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a dithiodipyrophosphate dispersion: adding 4g of magnesium aluminum silicate, 0.4g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.2g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a magnesium aluminum silicate dispersion; S2. Add 100 g of cellulose to 1000 g of sodium hydroxide aqueous solution (the mass concentration of sodium hydroxide aqueous solution is 5%), stir evenly, then add dithiopyrophosphate dispersion and magnesium aluminum silicate dispersion, stir evenly, vacuum degassing for 1 hour, and then spin through a wet spinning machine to obtain viscose fiber.
[0040] Example 9 The difference between Example 9 and Example 4 is that thiopyrophosphate and magnesium aluminum silicate are further added during the preparation of viscose fiber. The preparation method of viscose fiber comprises the following steps: The preparation method of viscose fiber comprises the following steps: S1, adding 18g of dithiodipyrophosphate, 1.6g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.8g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a dithiodipyrophosphate dispersion: adding 5g of magnesium aluminum silicate, 0.4g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.2g of castor oil polyoxyethylene ether nonionic dispersant to 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a magnesium aluminum silicate dispersion; S2. Add 100 g of cellulose to 1000 g of sodium hydroxide aqueous solution (the mass concentration of sodium hydroxide aqueous solution is 5%), stir evenly, then add dithiopyrophosphate dispersion and magnesium aluminum silicate dispersion, stir evenly, vacuum degassing for 1 hour, and then spin through a wet spinning machine to obtain viscose fiber.
[0041] Example 10 The difference between Example 10 and Example 9 is that the mass ratio of cellulose: dithiodipyrophosphate: magnesium aluminum silicate is 10:1.8:0.2.
[0042] Embodiment 11 The difference between Example 11 and Example 9 is that the mass ratio of cellulose: dithiodipyrophosphate: magnesium aluminum silicate is 10:1.8:0.8.
[0043] Example 12 The difference between Example 12 and Example 9 is that the mass ratio of cellulose: dithiodipyrophosphate: magnesium aluminum silicate is 10:1.4:0.5.
[0044] Example 13 The difference between Example 13 and Example 9 is that the mass ratio of cellulose: dithiodipyrophosphate: magnesium aluminum silicate is 10:2.2:0.5.
[0045] Embodiment 14 The difference between Example 14 and Example 9 is that the viscose fiber is prepared by modification, and the modification preparation method of the viscose fiber comprises the following steps: 3g of sodium carboxymethyl cellulose, 3g of citric acid and 1g of sodium hypophosphite were added into 250g of deionized water and mixed, and then cross-linked at 90°C for 2h. Then, 10g of viscose fiber was added and subjected to infiltration and diffusion treatment for 1h, and then dried at 80°C for 5min to obtain modified viscose fiber.
[0046] Embodiment 15 The difference between Example 15 and Example 9 is that the viscose fiber is prepared by modification, and the modification preparation method of the viscose fiber comprises the following steps: 5g of sodium carboxymethyl cellulose, 3g of citric acid and 1g of sodium hypophosphite were added to 250g of deionized water and mixed, and then cross-linked at 90°C for 2h. Then, 10g of viscose fiber was added and infiltrated and diffused for 1h, and then dried at 80°C for 5min to obtain modified viscose fiber.
[0047] Example 16 The difference between Example 16 and Example 9 is that the viscose fiber is prepared by modification, and the modification preparation method of the viscose fiber comprises the following steps: 4g of sodium carboxymethyl cellulose, 3g of citric acid and 1g of sodium hypophosphite were added to 250g of deionized water and mixed, and then cross-linked at 90°C for 2h. Then, 10g of viscose fiber was added and subjected to infiltration and diffusion treatment for 1h, and then dried at 80°C for 5min to obtain modified viscose fiber.
[0048] Embodiment 17 The difference between Example 17 and Example 16 is that the mass ratio of viscose fiber to sodium carboxymethyl cellulose is 1:0.2.
[0049] Embodiment 18 The difference between Example 18 and Example 16 is that the mass ratio of viscose fiber to sodium carboxymethyl cellulose is 1:0.6.
[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the stretching bath includes an aqueous solution of barium chloride, wherein the preparation method of the aqueous solution of barium chloride includes the following steps: adding 50g of barium chloride to 1000g of deionized water, stirring evenly, and heating to 15°C to obtain an aqueous solution of barium chloride.
[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 9 is that thiopyrophosphate is further added during the preparation of viscose fiber. The preparation method of viscose fiber comprises the following steps: The preparation method of viscose fiber comprises the following steps: S1, adding 18g of dithiopyrophosphate, 1.6g of tallow amine polyoxyethylene ether nonionic dispersant, and 0.8g of castor oil polyoxyethylene ether nonionic dispersant into 40g of deionized water, and dispersing them evenly with a vertical dispersant to obtain a dithiopyrophosphate dispersion; S2. Add 100 g of cellulose to 1000 g of sodium hydroxide aqueous solution (the mass concentration of sodium hydroxide aqueous solution is 5%), stir evenly, then add dithiopyrophosphate dispersion, stir evenly, vacuum degassing for 1 hour, and then spin through a wet spinning machine to obtain viscose fiber.
[0052] Performance testing: 1. Flame retardant properties According to GB / T5454-1997 "Textile Combustion Performance Test Oxygen Index Method", the fabrics in each embodiment and comparative example were cut into 1.5 cm×2 cm and then tested for the limiting oxygen index. The test results are recorded in Table 1, where the larger the limiting oxygen index, the better the flame retardant effect.
[0053] 2. Mechanical properties According to GB / T14343-2008, the fabrics in each embodiment and comparative example were cut into 1.5 cm×2 cm and then subjected to a breaking strength test. The test results are recorded in Table 1, wherein the higher the breaking strength, the better the mechanical properties of the fabric.
[0054] Table 1 Data analysis Specifically combining the test results of Examples 2-4 and Example 1, the mechanical properties of Examples 2-4 are better than those of Example 1. The analysis is as follows: the difference between Examples 2-4 and Example 1 is that glutamine is added during the preparation of carrageenan fibers, and glutamine can be filled in the network cross-linked structure that epichlorohydrin can form with carrageenan, thereby improving the strength of carrageenan and further improving the mechanical properties of the fabric.
[0055] Specifically combining the test results of Examples 7-9 and Example 4, the flame retardant properties and mechanical properties of Examples 7-9 are better than those of Example 4. The analysis is as follows: the difference between Examples 7-9 and Example 4 is that dithiopyrophosphate and magnesium aluminum silicate are added during the preparation of viscose fiber. On the one hand, the carbon layer generated by dithiopyrophosphate and the inorganic substance formed by magnesium aluminum silicate form a dense composite barrier, and the silicon element in magnesium aluminum silicate is covered with a silicon layer on the surface of the carbon layer after heating, thereby improving the flame retardant properties of the viscose fiber, and then improving the flame retardant properties of the fabric.
[0056] In addition, cellulose macromolecules will enter between the magnesium aluminum silicate crystal layers to form a network structure, thereby improving the mechanical properties of viscose fibers and thus the mechanical properties of the fabric.
[0057] Specifically combining the test results of Examples 14-16 and Example 9, the mechanical properties of Examples 14-16 are better than those of Example 9. The analysis is as follows: the difference between Examples 14-16 and Example 9 is that the carrageenan fiber grafts sodium carboxymethyl cellulose onto the viscose fiber through citric acid, so that the surface of the viscose fiber is negatively charged, and the surface of the carrageenan fiber contains metal ions, which are positively charged. Therefore, through the principle of mutual attraction between positive and negative charges, the binding force between the carrageenan fiber and the viscose fiber is effectively improved, thereby improving the mechanical properties of the fabric.
[0058] Specifically combining the test results of Example 1 and Comparative Example 1, the mechanical properties of Example 1 are better than those of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that the carrageenan fiber is treated with an epichlorohydrin solution to increase the strength of the carrageenan fiber, thereby improving the mechanical properties of the fabric.
[0059] Specifically combining the test results of Example 9 and Comparative Example 2, Example 9 has better flame retardant properties and mechanical properties than Comparative Example 2. The analysis is as follows: the difference between Example 9 and Comparative Example 2 is that in addition to dithiopyrophosphate, magnesium aluminum silicate is also added in the preparation process of viscose fiber, and the inorganic matter formed by magnesium aluminum silicate and the carbon layer generated by dithiopyrophosphate form a dense composite barrier, and the silicon element in magnesium aluminum silicate is covered with a silicon layer on the surface of the carbon layer after heating, thereby improving the flame retardant properties of the viscose fiber, and then improving the flame retardant properties of the fabric.
[0060] In addition, cellulose macromolecules will enter between the magnesium aluminum silicate crystal layers to form a network structure, thereby improving the mechanical properties of viscose fibers and then improving the mechanical properties of the fabric.
[0061] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A flame retardant fabric, comprising a fabric body, characterized in that: The fabric body comprises carrageenan fibers and viscose fibers; The preparation method of the carrageenan fiber comprises the following steps: The carrageenan and the sodium hydroxide aqueous solution are mixed, stirred evenly, and then subjected to a degassing treatment to obtain a spinning solution, and then the spinning solution is spun into a coagulation bath and a stretching bath, and then soaked, washed, and dried to obtain carrageenan fibers; the coagulation bath is a barium chloride aqueous solution; The method for preparing the viscose fiber comprises the following steps: The cellulose and sodium hydroxide aqueous solution are mixed, stirred evenly, vacuum degassed, and then spun to obtain viscose fiber.
2. The flame retardant fabric according to claim 1, characterized in that: The stretching bath is an epichlorohydrin solution.
3. The flame retardant fabric according to claim 2, characterized in that: Glutamine is also added in the preparation process of the carrageenan fiber. The preparation method of the carrageenan fiber comprises the following steps: The carrageenan and sodium hydroxide aqueous solution are mixed and stirred evenly, and then glutamine is added and stirred evenly, and then deaerated to obtain a spinning solution, and then the spinning solution is spun and then enters a coagulation bath and a stretching bath, and then soaked, washed, and dried to obtain carrageenan fibers.
4. The flame retardant fabric according to claim 3, characterized in that: The mass ratio of the carrageenan to glutamine is 1:(0.2-0.3).
5. The flame retardant fabric according to claim 1, characterized in that: During the preparation process of the viscose fiber, dithiopyrophosphate and magnesium aluminum silicate are also added. The preparation method of the viscose fiber comprises the following steps: S1. Add dithiopyrophosphate, tallow amine polyoxyethylene ether nonionic dispersant, and castor oil polyoxyethylene ether nonionic dispersant to deionized water, and stir evenly to obtain a dithiopyrophosphate dispersion; add magnesium aluminum silicate, tallow amine polyoxyethylene ether nonionic dispersant, and castor oil polyoxyethylene ether nonionic dispersant to deionized water, and stir evenly to obtain a magnesium aluminum silicate dispersion; S2. Add cellulose to a sodium hydroxide aqueous solution, stir evenly, then add a dithiopyrophosphate dispersion and a magnesium aluminum silicate dispersion, stir evenly, vacuum degas, and then spin to obtain viscose fiber.
6. The flame retardant fabric according to claim 5, characterized in that: The mass ratio of the cellulose, dithiopyrophosphate and magnesium aluminum silicate is 10: (1.6-2.0): (0.4-0.6).
7. The flame retardant fabric according to claim 1, characterized in that: The viscose fiber is prepared by modification, and the modification preparation method of the viscose fiber comprises the following steps: Sodium carboxymethyl cellulose, citric acid and sodium hypophosphite are added into deionized water, and after the reaction is completed, viscose fiber is added and dried to obtain modified viscose fiber.
8. The flame retardant fabric according to claim 7, characterized in that: The mass ratio of the viscose fiber to sodium carboxymethyl cellulose is 1:(0.3-0.5).
9. A method for preparing the flame retardant fabric according to claim 1, characterized in that: The steps include: The flame retardant fabric is produced by blending carrageenan fiber and viscose fiber.